Ketimpangan Gender pada Dongeng La Barbe Bleue Karya Charles Perrault - Pratama, Dian Agustina (Sekolah Tinggi Bahasa Asing Yapari-ABA, 2023)
Gender inequality is something that often becomes a public concern, including in the literature. Therefore, this research aims to reveal the form of gender inequality in the fairy tale La Barbe Bleue by Charles Perrault. Gender inequality is seen in the patriarchal system, seeing men with masculine values have a higher position than women based on social class in a patriarchal society. The aim of this research is to describe the forms of gender inequality that appear in the fairy tale La Barbe Bleue. This study used a descriptive qualitative method. The data collected in the fairy tale La Barbe Bleue are all words or sentences that fulfill elements of gender inequality. The data collection technique used was reading and recording the fairy tale La Barbe Bleue. The research results show that gender inequality appears in the form of 2 subordinations, 3 violence and 2 marginalization in the fairy tale La Barbe Bleue based on differences in social class in the fairy tale setting.